ETOS KERJA PENDIDIK TAMAN KANAK-KANAK SEKECAMATAN CERENTI KABUPATEN KUANTAN SINGINGI - Witri, Susila; Risma, Devi; ', Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The research was aimed to knew the described work ethic educators Kindergarten Cerenti District in Kuantan Singingi Regency. The population and sample research was totally 34 educators Kindergarten Cerenti District in Kuantan Singingi Regency. The technique of collecting data used questioners Likert scale and use correlation analyzing Pearson Product Moment. Technique analyze data is use trial scale and analyze statistic method by SPSS Program for Windows 17 Ver. Based on research value is use correlation Analyzing Pearson Product Moment to be able to knew confidence 744 score by 60,7% is enough category, team work 789 By 57,9 % is enough category, hard work 716 by 65,7% is well category, seriousness indicators 407 by 59,8% is enough category. Overall the work ethnic of educator Kindergarten got 61,0% percentage in both category is 61%-80%.Key Words : Word Ethic, Educators